Aortic homograft implantation after Ozaki procedure: Case report - Komarov, Roman (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: The infective endocarditis incidence data for patients undergoing aortic valve neocuspidization with glutaraldehyde-treated autologous pericardium (Ozaki procedure) are rare, and the optimal surgical treatment strategy remains unclear. CASE PRESENTATION: This is the first case report of surgical treatment of infective endocarditis of aortic valve with cryopreserved homograft in an athlete with previously performed Ozaki procedure. CLINICAL DISCUSSION: The choice of homograft was dictated by the young age of the patient; professional activity as an athlete; refusal of anticoagulants and the need for wide excision of compromised tissues to mitigate potential risk of spread of infection as well as its recurrence. CONCLUSION: The use of the aortic homograft allowed us to radically remove the infected tissues and achieve hemodynamic characteristics similar to the native valve. This is probably the first case report of use of homograft to treat aortic valve endocarditis following Ozaki procedure.